Effects of Long-Term Paired Associative Stimulation on Strength of Leg Muscles and Walking in Chronic Tetraplegia: A Proof-of-Concept Pilot Study - Rodionov, Andrei; Savolainen, Sarianna; Kirveskari, Erika; Mäkelä, Jyrki P.; Shulga, Anastasia (Frontiers in Neurology, 2020)
Recovery of lower-limb function after spinal cord injury (SCI) depends on the extent of remaining neural transmission in the corticospinal pathway. The aim of this study was to explore the effects of long-term paired-associative stimulation (PAS) on leg muscle strength and walking in people with SCI. Five individuals with traumatic incomplete chronic tetraplegia (>34 months postinjury, American Spinal Injury Association Impairment Scale (AIS) D, 3 females, mean age 60) with no contraindications to transcranial magnetic stimulation (TMS) received PAS to one or both legs for 2 months (28 sessions in total, 5 times a week for first 2 weeks and 3 times a week after that). The participants were evaluated with the Manual muscle test (MMT), AIS motor and sensory examination, the Modified Asworth Scale (MAS), and the Spinal Cord Independence Measure (SCIM) prior the intervention, after 1 and 2 months of stimulations, and after a 1-month follow-up. The study was registered at the clinicaltrials.gov (NCT03459885). During the intervention, MMT scores and AIS motor scores increased significantly (p = 0.014 and p = 0.033, respectively). Improvements were stable in the follow-up. AIS sensory scores, MAS and SCIM were not modified significantly. MMT score prior the intervention was a good predictor of changes in walking speed (r2adj=0,962). The results of this proof-of-concept pilot study imply that long-term PAS can be potentially effective for improvement of leg muscle strength and walking in people with chronic incomplete SCI, and that a larger trial is feasible and justified.